An electrochemical method for preparing a porous copper foil for lithium ion negative electrode current collector

CN116590781BActive Publication Date: 2026-10-20YICHUN JIANGLI LITHIUM BATTERY NEW ENERGY IND RES INST +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310708450.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2026-10-20
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

现有电化学脱合金法在实际应用中有下列缺陷:采用单一强酸或混合强酸作为电解液,脱合金后的废液处理比较困难,对环境影响较大;由于其采用的电解液腐蚀性较强,刻蚀出的多孔铜的孔径、形貌难以控制,且多孔铜的表面易氧化

Benefits of technology

[0019](1)本发明采用特定配比的电解液,通过电化学脱合金法制备的多孔铜的表面光洁明亮,具有很好的抗氧化性,同时形貌、孔径的控制更精确,能够直接以市售铜合金为原料,得到孔隙率为30~45%、孔径为0.1μm-8μm的多孔铜箔,可实现连续生产,降低成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116590781B_ABST
    Figure CN116590781B_ABST
Patent Text Reader

Abstract

The application discloses an electrochemical preparation method of a porous copper foil for a lithium ion negative electrode current collector, and comprises the following steps: removing impurities and an oxide layer on the surface of a Cu-X alloy sheet; preparing an electrolyte; mixing the electrolyte according to the following mass fractions: 25-35 parts of sulfuric acid, 55-65 parts of phosphoric acid, 4.5-5.5 parts of deionized water, 2.5-3.5 parts of ethanol, 1.5-2.0 parts of urea and 0.1-0.3 parts of benzotriazole; taking the Cu-X alloy sheet as a working electrode, taking a nickel sheet or a platinum sheet as a counter electrode, taking a saturated calomel electrode as a reference electrode, and taking the above-prepared solution as an electrolyte to form a three-electrode system; and obtaining the porous copper current collector through an electrochemical dealloying method. The application is more accurate in the control of the morphology and pore diameter of the porous copper foil, can directly use a commercially available copper alloy as a raw material, reduces the cost, can effectively inhibit the growth of lithium dendrites in the charging and discharging process, and reduces the volume change in the charging and discharging cycle process of the metal lithium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical technology and relates to an electrochemical preparation method of porous copper foil for lithium-ion negative electrode current collectors. Background Technology

[0002] Currently, commercially available copper foil current collectors are electrolytic copper foils with smooth, single-sided rough, and double-sided rough surfaces, all with relatively low surface roughness. Neither the amount of active material they can hold nor the surface area available for lithium intercalation and deintercalation is sufficient for high-capacity, high-power lithium-ion battery applications. One strategy to address this issue is to fabricate porous / hollow copper foil current collectors. Porous metal materials not only provide a larger buffer space for volume changes in the negative electrode active material, enhancing the bonding force between the active material and the current collector, thus improving battery cycle performance, but also increase the surface area of ​​contact between the current collector and the active material, allowing for the inclusion of more active material and simultaneously increasing capacity and charge / discharge rate.

[0003] There are many methods for preparing nanoporous copper foil current collectors. Currently, the main methods include metal powder sintering, template methods, and dealloying. Dealloying, as a widely used method, can be further subdivided into chemical dealloying, vacuum distillation dealloying, and electrochemical dealloying, each imparting different characteristics to the current collector. Vacuum distillation and electrochemical dealloying are more environmentally friendly than chemical dealloying, but vacuum distillation requires higher temperatures and is energy-intensive. Besides consuming concentrated acid and the difficulty in controlling pore size and distribution, chemical dealloying is relatively easy to scale up. Conversely, electrochemical dealloying can be considered a green and controllable method, capable of precisely etching uniform and smooth porous structures. Existing electrochemical dealloying methods have the following drawbacks in practical applications: using a single strong acid or a mixture of strong acids as the electrolyte makes wastewater treatment after dealloying difficult and has a significant environmental impact; due to the strong corrosiveness of the electrolyte, the pore size and morphology of the etched porous copper are difficult to control, and the surface of the porous copper is easily oxidized. Summary of the Invention

[0004] To address the aforementioned issues, this invention provides an electrochemical preparation method for porous copper foil used as a lithium-ion negative electrode current collector. This method allows for more precise control over the morphology and pore size of the porous copper foil, and enables the direct use of commercially available copper alloys as raw materials, thereby reducing costs. Furthermore, it effectively inhibits the growth of lithium dendrites during charge and discharge processes, thereby reducing volume changes during lithium metal charge and discharge cycles.

[0005] The technical solution adopted in this invention is an electrochemical preparation method of porous copper foil for lithium-ion negative electrode current collectors, comprising the following steps:

[0006] Step 1: Remove impurities and oxide layers from the surface of the Cu-X alloy sheet;

[0007] Step 2: Prepare the electrolyte solution; the electrolyte solution is mixed according to the following mass parts: 25-35 parts sulfuric acid, 55-65 parts phosphoric acid, 4.5-5.5 parts deionized water, 2.5-3.5 parts ethanol, 1.5-2.0 parts urea and 0.1-0.3 parts benzotriazole;

[0008] Step 3: Using a Cu-X alloy sheet as the working electrode, a nickel or platinum sheet as the counter electrode, a saturated calomel electrode as the reference electrode, and the solution prepared in Step 2 as the electrolyte, a three-electrode system is formed; a porous copper current collector is obtained by electrochemical dealloying.

[0009] Furthermore, the Cu-X alloy is Cu-Zn, Cu-Mn, Cu-Al, Cu-Co, Cu-Sn, or Cu-Ni.

[0010] Furthermore, in the Cu-X alloy sheet, the atomic mass percentage of Cu in the alloy is 30% to 70%.

[0011] Furthermore, the thickness of the Cu-X alloy sheet is 20–100 μm.

[0012] Furthermore, the Cu-X alloy is a commercially available copper alloy.

[0013] Furthermore, in step three, the electrochemical dealloying method is a constant current method, a constant voltage method, or a square wave cyclic pulse method.

[0014] Furthermore, the cutoff voltage of the square wave cyclic pulse method is -0.4 to 1.0V, the number of cycles is 20 to 80, and the temperature of the electrolyte is room temperature.

[0015] Furthermore, in step three, the pore size and porosity of the porous copper current collector are controlled by dual regulation of alloy composition and electrochemical etching amount.

[0016] Furthermore, the pores of the obtained porous copper current collector are through holes and / or blind holes, with a porosity of 30-45% and a pore diameter of 0.1μm-8μm.

[0017] Furthermore, step one includes: ultrasonically cleaning the Cu-X alloy sheet in anhydrous ethanol, acetone or toluene for 5 to 10 minutes, then cleaning it with deionized water and drying it.

[0018] The beneficial effects of this invention are:

[0019] (1) The present invention uses an electrolyte with a specific ratio to prepare porous copper by electrochemical dealloying. The surface of the porous copper is smooth and bright, with good oxidation resistance. At the same time, the morphology and pore size are more precisely controlled. It can directly use commercially available copper alloys as raw materials to obtain porous copper foil with a porosity of 30-45% and a pore size of 0.1μm-8μm, which can realize continuous production and reduce costs.

[0020] (2) The porous copper foil prepared by the present invention has a continuous three-dimensional pore structure, which increases the specific surface area of ​​the electrode and reduces the effective current density of the electrode, thereby suppressing the generation of lithium dendrites and slowing down the volume change of the lithium metal anode during the charging and discharging process, thus obtaining a volume stable lithium metal anode.

[0021] (3) The present invention can adjust the pore size by controlling the alloy composition and the amount of electrochemical etching. The preparation method is simple, low cost, and can realize the large-scale application of porous copper current collectors. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This is a SEM image of the porous copper current collector prepared in Example 1 of the present invention.

[0024] Figure 2 This is a SEM image of the porous copper current collector prepared in Example 2 of the present invention.

[0025] Figure 3 This is a SEM image of the porous copper current collector prepared in Example 3 of the present invention.

[0026] Figure 4 This is a SEM image of the porous copper current collector prepared in Example 4 of the present invention.

[0027] Figure 5 This is a SEM image of the porous copper current collector prepared in Example 5 of the present invention.

[0028] Figure 6 This is a SEM image of the porous copper current collector prepared in Comparative Example 2 of this invention.

[0029] Figure 7 This is a SEM image of the porous copper current collector prepared in Comparative Example 3 of this invention. Detailed Implementation

[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0031] Example 1,

[0032] An electrochemical preparation method for porous copper foil for lithium-ion anode current collectors includes the following steps:

[0033] Step 1: Cut the 20μm thick Cu-Zn alloy sheet into 2cm×2cm thin sheets, ultrasonically clean them in toluene for 5 minutes, then clean them with deionized water and dry them to remove impurities and oxide layers from the surface of the Cu-Zn alloy sheet; the atomic mass ratio of Cu in the Cu-Zn alloy sheet is 40%.

[0034] Step 2: Prepare the electrolyte solution. The electrolyte solution is mixed according to the following mass fractions: 30% sulfuric acid, 60% phosphoric acid, 5% deionized water, 3% ethanol, 1.8% urea, and 0.2% benzotriazole.

[0035] Step three involves using a Cu-Zn alloy sheet as the working electrode, a platinum sheet as the counter electrode, a saturated calomel electrode as the reference electrode, and the solution prepared in step two as the electrolyte to form a three-electrode system. Electrochemical corrosion is performed using a 20mA constant current method in a CHI760 electrochemical workstation at room temperature to obtain a porous copper current collector. The magnitude of the current and the time are determined based on the sample size and the elemental composition of the alloy.

[0036] The prepared porous copper current collector was first washed with deionized water, then with anhydrous ethanol, and finally vacuum dried at room temperature. The porosity of this porous copper current collector is 30%, the pore size is 0.1 μm-8 μm, and the pores are through pores and / or blind pores, such as... Figure 1 As shown.

[0037] Example 2,

[0038] An electrochemical preparation method for porous copper foil used as a lithium-ion negative electrode current collector includes the following steps:

[0039] Step 1: Cut the 50μm thick Cu-Zn alloy sheet into 2cm×2cm thin sheets, ultrasonically clean them in acetone for 10min, then clean them with deionized water and dry them to remove impurities and oxide layers from the surface of the Cu-Zn alloy sheet; the atomic mass ratio of Cu in the Cu-Zn alloy sheet is 30%.

[0040] Step 2: Prepare the electrolyte solution. The electrolyte solution is mixed according to the following mass fractions: 30% sulfuric acid, 60% phosphoric acid, 5% deionized water, 3% ethanol, 1.8% urea, and 0.2% benzotriazole.

[0041] Step three involves using a Cu-Zn alloy sheet as the working electrode, a platinum sheet as the counter electrode, a saturated calomel electrode as the reference electrode, and the solution prepared in step two as the electrolyte to form a three-electrode system. Electrochemical corrosion is performed using a constant voltage method of 0.6V in a CHI760 electrochemical workstation at room temperature to obtain a porous copper current collector. The voltage and time are determined based on the sample size and alloy element content; higher voltage results in shorter time, but the voltage should generally not be too high, otherwise the corrosion rate will be too fast and uncontrollable.

[0042] The prepared porous copper current collector was first washed with deionized water, then with anhydrous ethanol, and finally vacuum dried at room temperature. The porous copper current collector has a porosity of 35%, a pore size of 0.1 μm-8 μm, and the pores are through pores and / or blind pores, such as... Figure 2 As shown.

[0043] Example 3,

[0044] An electrochemical preparation method for porous copper foil used as a lithium-ion negative electrode current collector includes the following steps:

[0045] Step 1: Cut a 100μm thick Cu-Zn alloy sheet into 2cm×2cm thin sheets, ultrasonically clean them in anhydrous ethanol for 10min, then clean them with deionized water and dry them to remove impurities and oxide layers from the surface of the Cu-Zn alloy sheet; the atomic mass ratio of Cu in the Cu-Zn alloy sheet is 30%.

[0046] Step 2: Prepare the electrolyte solution. The electrolyte solution is mixed according to the following mass fractions: 30% sulfuric acid, 60% phosphoric acid, 5% deionized water, 3% ethanol, 1.8% urea, and 0.2% benzotriazole.

[0047] Step 3: A three-electrode system was formed using a Cu-Zn alloy sheet as the working electrode, a platinum sheet as the counter electrode, a saturated calomel electrode as the reference electrode, and a solution prepared with S2 as the electrolyte. In a CHI760 electrochemical workstation, a square wave cyclic pulse method was used, with a cutoff voltage ranging from -0.2V to 0.8V, 50 cycles, and the electrolyte temperature at room temperature (18–25℃), to obtain a porous copper current collector.

[0048] The prepared porous copper current collector was first washed with deionized water, then with anhydrous ethanol, and finally vacuum dried at room temperature. The porosity of this porous copper current collector was 40%, with pore sizes ranging from 0.1 μm to 8 μm. The pores were through-holes and / or blind-holes, such as... Figure 3 As shown.

[0049] Example 4,

[0050] An electrochemical preparation method for porous copper foil used as a lithium-ion negative electrode current collector includes the following steps:

[0051] Step 1: Cut the 80μm thick Cu-Ni alloy sheet into 2cm×2cm thin sheets, ultrasonically clean them in anhydrous ethanol for 10min, then clean them with deionized water and dry them to remove impurities and oxide layers from the surface of the Cu-Ni alloy sheet; the atomic mass ratio of Cu in the Cu-Ni alloy sheet is 40%.

[0052] Step 2: Prepare the electrolyte solution. The electrolyte solution is mixed according to the following mass proportions: 25 parts sulfuric acid, 65 parts phosphoric acid, 5.5 parts deionized water, 2.5 parts ethanol, 2.0 parts urea, and 0.1 parts benzotriazole.

[0053] Step 3: A three-electrode system was formed using a Cu-Zn alloy sheet as the working electrode, a platinum sheet as the counter electrode, a saturated calomel electrode as the reference electrode, and a solution prepared with S2 as the electrolyte. In a CHI760 electrochemical workstation, a square wave cyclic pulse method was used, with a cutoff voltage ranging from -0.2V to 0.6V, 50 cycles, and the electrolyte temperature at room temperature, to obtain a porous copper current collector.

[0054] The prepared porous copper current collector was first washed with deionized water, then with anhydrous ethanol, and finally vacuum dried at room temperature. The porosity of this porous copper current collector is 30%, the pore size is 0.1 μm-8 μm, and the pores are through pores and / or blind pores, such as... Figure 4 As shown.

[0055] Example 5,

[0056] An electrochemical preparation method for porous copper foil used as a lithium-ion negative electrode current collector includes the following steps:

[0057] Step 1: Cut the 80μm thick Cu-Mn alloy sheet into 2cm×2cm thin sheets, ultrasonically clean them in anhydrous ethanol for 10min, then clean them with deionized water and dry them to remove impurities and oxide layers from the surface of the Cu-Mn alloy sheet; the atomic mass ratio of Cu in the Cu-Mn alloy sheet is 70%.

[0058] Step 2: Prepare the electrolyte solution. The electrolyte solution is mixed according to the following mass fractions: 35 parts sulfuric acid, 55 parts phosphoric acid, 4.5 parts deionized water, 3.5 parts ethanol, 1.5 parts urea and 0.3 parts benzotriazole.

[0059] Step 3: A three-electrode system was formed using a Cu-Zn alloy sheet as the working electrode, a platinum sheet as the counter electrode, a saturated calomel electrode as the reference electrode, and a solution prepared with S2 as the electrolyte. In a CHI760 electrochemical workstation, a square wave cyclic pulse method was used, with a cutoff voltage ranging from -0.2V to 0.6V, 50 cycles, and the electrolyte temperature at room temperature, to obtain a porous copper current collector.

[0060] The prepared porous copper current collector was first washed with deionized water, then with anhydrous ethanol, and finally vacuum dried at room temperature. The porous copper current collector has a porosity of 25%, a pore size of 0.1 μm-8 μm, and the pores are through pores and / or blind pores, such as... Figure 5 As shown.

[0061] from Figure 1-5 It can be seen that the porous copper prepared in Examples 1-5 of the present invention has a clean surface, high porosity, uniform pore size, tight pores, and good interconnectivity.

[0062] Comparative Example 1,

[0063] Using a Cu-40%Zn alloy sheet (Cu atomic percentage is 40%) as the current collector, the surface of the Cu-Zn alloy sheet is cleaned with ethanol to remove impurities from the surface of the alloy sheet, thus obtaining a two-dimensional copper foil.

[0064] In Examples 1-3 and Comparative Example 1, the Cu-Zn alloy sheets were prepared using commercially available brass. Commercially available Cu-Zn alloys differ significantly from laboratory-prepared Cu-Zn alloys, primarily in terms of compositional uniformity, Zn content, and impurity content control. Examples 1-5 of this invention directly use commercially available brass (Cu-Zn alloy) to prepare porous copper foil. The raw materials are readily available, and the industrialization prospects are excellent. However, using commercially available brass to prepare porous copper foil mainly suffers from poor compositional uniformity, high impurity content, and low zinc content, leading to unstable process technology. But its main advantage in practical application is that this process can be directly applied to the preparation of porous copper from ordinary brass, enabling continuous production and reducing costs.

[0065] Comparative Example 2,

[0066] An electrochemical preparation method for porous copper foil used as a lithium-ion negative electrode current collector includes the following steps:

[0067] Step 1: Cut a commercially available brass (Cu-30%Zn) alloy sheet with a thickness of 50μm into a 2cm×2cm sheet, ultrasonically clean it in anhydrous ethanol for 10min, then clean it with deionized water and dry it to remove impurities and oxide layer from the surface of the Cu-Zn alloy sheet.

[0068] Step 2: Use a 0.5 mol / L hydrochloric acid solution as the electrolyte.

[0069] Step 3: A three-electrode system was formed using a Cu-Zn alloy sheet as the working electrode, a platinum sheet as the counter electrode, a saturated calomel electrode as the reference electrode, and a solution prepared with S2 as the electrolyte. In a CHI760 electrochemical workstation, a square wave cyclic pulse method was used, with a cutoff voltage ranging from -0.2V to 0.8V, 50 cycles, and the electrolyte temperature at room temperature (18–25℃), to obtain a porous copper current collector.

[0070] The prepared porous copper current collector was first washed with deionized water, then with anhydrous ethanol, and finally vacuum dried at room temperature. The porosity of this porous copper current collector is 18%, the pore size is 0.1 μm-8 μm, and the pores are through pores and / or blind pores, such as... Figure 6 As shown.

[0071] Comparative Example 3,

[0072] An electrochemical preparation method for porous copper foil used as a lithium-ion negative electrode current collector includes the following steps:

[0073] Step 1: Cut a commercially available brass (Cu-30%Zn) alloy sheet with a thickness of 50μm into a 2cm×2cm sheet, ultrasonically clean it in anhydrous ethanol for 10min, then clean it with deionized water and dry it to remove impurities and oxide layer from the surface of the Cu-Zn alloy sheet.

[0074] Step 2: Use a 0.4 mol / L sulfuric acid solution as the electrolyte.

[0075] Step 3: A three-electrode system was formed using a Cu-Zn alloy sheet as the working electrode, a platinum sheet as the counter electrode, a saturated calomel electrode as the reference electrode, and a solution prepared with S2 as the electrolyte. In a CHI760 electrochemical workstation, a square wave cyclic pulse method was used, with a cutoff voltage ranging from -0.2V to 0.8V, 50 cycles, and the electrolyte temperature at room temperature (18–25℃), to obtain a porous copper current collector.

[0076] The prepared porous copper current collector was first washed with deionized water, then with anhydrous ethanol, and finally vacuum dried at room temperature. The porosity of this porous copper current collector was 20%, the pore size was 0.1 μm-8 μm, and the pores were through pores and / or blind pores, such as... Figure 7 As shown.

[0077] from Figure 6-7 It can be seen that the porous copper prepared in Comparative Examples 2-3 has poor surface cleanliness, low porosity, poor pore size uniformity, and poor connectivity.

[0078] Metallic Li was deposited onto the current collectors prepared in Examples 1-5, and then the electrode with deposited metallic Li was assembled with an LFP (lithium iron phosphate) positive electrode to form a full cell. The assembled lithium metal full cells are denoted as S, with the full cell assembled from the two-dimensional copper foil obtained in Comparative Example 1 being denoted as S. V The full cells assembled with porous copper prepared in Examples 1-5 are respectively designated as S1 to S5.

[0079] Test numbers are S1-S5 and S V The results of the coulombic efficiency and cycle performance of the full cell are shown in Table 1.

[0080] Table 1. Test results of coulombic efficiency and cycle performance of the full cell.

[0081] <![CDATA[S V ]]> 90.3% 87.3% <![CDATA[S1]]> 95.2% 90.6% <![CDATA[S2]]> 96.8% 91.8% <![CDATA[S3]]> 99.4% 98.2% <![CDATA[S4]]> 94.3% 90.2% <![CDATA[S5]]> 95.8% 92.6%

[0082] As shown in Table 1, the battery using the current collector of this invention exhibits better coulombic efficiency and cycle performance, with both coulombic efficiency and capacity retention exceeding those of traditional two-dimensional copper foil. Furthermore, practical experience demonstrates that the battery using the current collector of this invention possesses superior safety performance.

[0083] In the embodiments of the present invention, the alloy sheet is Cu-Zn, Cu-Mn, Cu-Al, Cu-Co, Cu-Sn or Cu-Ni, and the atomic mass percentage of Cu in the alloy is 30% to 70%. If the atomic percentage of Cu is less than 30%, the porosity of the obtained porous copper is very low and cannot meet the requirements; if the atomic percentage of Cu is higher than 70%, the mechanical properties of the obtained porous copper are very poor and cannot meet the requirements of lithium battery current collectors.

[0084] When the alloy sheet is a Cu-Zn alloy, the resulting porous copper surpasses other alloys in terms of morphology, pore size, and porosity. This is mainly because, in addition to the selective dissolution of Zn within the alloy, both zinc and copper can dissolve simultaneously. Zinc ions remain in the electrolyte, while copper ions are redeposited on the alloy surface through a cathode corrosion process. Therefore, porous copper prepared using Cu-Zn alloys yields superior results.

[0085] The thickness of the alloy sheet is 20-100 μm, determined according to the thickness requirements of the current collector for lithium batteries. If the thickness of the alloy sheet is less than 20 μm, the mechanical properties of the prepared porous copper foil are poor and it is relatively easy to break. If the thickness of the alloy sheet exceeds 100 μm, the Zn element cannot be completely and thoroughly corroded during electrochemical corrosion, resulting in impermeable and discontinuous pores. Moreover, the electrochemical corrosion time is long, making it difficult to achieve large-scale application of porous copper.

[0086] The square wave cyclic pulse method allows for precise control and stable process operation. Small fluctuations in various parameters have minimal impact on sample morphology. When using this method to prepare current collectors for further experiments or production, it can significantly reduce experimental errors and improve yield. The negative voltage of the square wave pulse cyclic method induces a dissolution-redeposition process on the sample surface, eliminating the adverse effects of spherical diffusion. In this embodiment, the process parameters for the square wave cyclic pulse method are: electrolyte temperature at room temperature, cutoff voltage of -0.4 to 1.0 V, and 30 to 80 cycles. Too low a cutoff voltage results in a slow corrosion rate, leaving excessive impurities in the pores; too high a cutoff voltage results in a fast corrosion rate, making it difficult to control porosity and pore morphology. Too few cycles result in incomplete corrosion, incomplete pore morphology, and low porosity. Too many cycles lead to excessive corrosion of the alloy, reducing its mechanical properties.

[0087] The electrolyte of this invention is a mixture of the following parts by mass: 25-35 parts sulfuric acid, 55-65 parts phosphoric acid, 4.5-5.5 parts deionized water, 2.5-3.5 parts ethanol, 1.5-2.0 parts urea, and 0.1-0.3 parts benzotriazole. In the electrolyte, sulfuric acid and phosphoric acid primarily act to corrode the alloy; deionized water primarily dilutes the acid; ethanol primarily acts as a corrosion inhibitor; urea primarily acts as a leveling agent; and benzotriazole primarily acts as a brightening agent. The addition of phosphoric acid reduces the acidity of the sulfuric acid, making the corrosion process gentler and more controllable.

[0088] This invention utilizes a Cu-X alloy sheet as a substrate and employs acid solutions and additives in different ratios as electrolytes. Porous copper current collectors with varying pore sizes are etched using an electrochemical method. These current collectors are then used as the negative electrode current collector in lithium metal batteries. This method effectively provides deposition space for lithium metal, restricts lithium dendrite growth, and reduces volume changes during lithium metal charge-discharge cycles. The resulting porous copper current collectors have through-holes and / or blind holes, with a porosity of 30–45% and pore sizes of 0.1 μm–8 μm. Excessively large pore sizes in the negative electrode current collector cannot suppress the growth of lithium dendrites, while excessively low porosity reduces lithium storage capacity and affects lithium storage performance.

[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of protection of the present invention.

Claims

1. An electrochemical preparation method for porous copper foil used as a lithium-ion negative electrode current collector, characterized in that, Includes the following steps: Step 1: Remove impurities and oxide layers from the surface of the Cu-X alloy sheet; Step 2: Prepare the electrolyte solution; the electrolyte solution is mixed according to the following mass proportions: 25-35 parts sulfuric acid, 55-65 parts phosphoric acid, 4.5-5.5 parts deionized water, 2.5-3.5 parts ethanol, 1.5-2.0 parts urea, and 0.1-0.3 parts benzotriazole; Step 3: Using a Cu-X alloy sheet as the working electrode, a nickel or platinum sheet as the counter electrode, a saturated calomel electrode as the reference electrode, and the solution prepared in Step 2 as the electrolyte, a three-electrode system is formed; a porous copper current collector is obtained by electrochemical dealloying. The pores of the obtained porous copper current collector are through holes and / or blind holes, with a porosity of 30~45%, a pore size of 0.1μm-8μm, and a continuous three-dimensional pore structure with a smooth and bright surface. In step three, the electrochemical dealloying method is the square wave cyclic pulse method; The cutoff voltage of the square wave cyclic pulse method is -0.4~1.0V, the number of cycles is 20~80, and the temperature of the electrolyte is room temperature. The Cu-X alloy is a commercially available copper alloy; The Cu-X alloy is Cu-Zn. In addition to the selective dissolution of Zn in the alloy, the zinc and copper in the alloy can also dissolve simultaneously. Zinc ions remain in the electrolyte, while copper ions are redeposited on the alloy surface through the process of corroding the cathode. In the Cu-X alloy sheet, the atomic mass percentage of Cu in the alloy is 30% to 70%; The thickness of the Cu-X alloy sheet is 20~100μm.

2. The electrochemical preparation method of porous copper foil for lithium-ion negative electrode current collector according to claim 1, characterized in that, In step three, the pore size and porosity of the porous copper current collector are controlled by both alloy composition and electrochemical etching amount.

3. The electrochemical preparation method of porous copper foil for lithium-ion negative electrode current collector according to claim 1, characterized in that, Step one includes: ultrasonically cleaning the Cu-X alloy sheet in anhydrous ethanol, acetone or toluene for 5-10 minutes, then cleaning it with deionized water and drying it.

Citation Information

Patent Citations

  • A method for preparing an anode porous copper current collector used for a lithium metal battery

    CN107293754A

  • Defect-rich copper-based nano-catalyst as well as preparation method and application thereof

    CN114635153A

  • Copper electrolytic polishing solution and electrolytic polishing method

    CN114990685A